(untitled) (Archive of Conferences, 2022)
The article discusses the structure of the Central Revolutionary Committee of the USSR and local revkom. On September 14, 1920, at the general meeting of the Council of People’s Ministers, the Revkom and the Central Committee of the CPSU, the All-Bukhara Revolutionary Committee (chairman Abdulkadir Muhitdinov) was formed, consisting of 9 members. Muinjon Aminov, Olimjon Akchurin, Abdulhamid Aripov, Sabir Yusupov, Hoji Hasan Ibrahimov, Fayzulla Khodjaev, Kulmuhamedov were appointed members of the Bukhara Revolutionary Committee. This article also discusses the activities of the above national leaders and personnel.